2022
DOI: 10.1002/cam4.4750
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre‐existing interstitial lung abnormal shadow on lung injury development and severity in patients of non‐small cell lung cancer treated with osimertinib

Abstract: Background: First-generation epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) sometimes causes lung injury, thereby affecting survival.Although pre-existing interstitial lung abnormal shadow (pre-ILS) increases the risk of lung injury by EGFR-TKIs, its impact on osimertinib, a third-generation EGFR-TKI, remains unknown. Patients and Methods:This retrospective cohort study consecutively enrolled patients of EGFR-mutated non-small cell lung cancer treated with osimertinib.Computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In the present study, cause-specific HRs for AEIP were observed to increase sequentially with an increase in the ILA score. These findings are consistent with those shown in prior research that reported increased odds ratios for AEIP in patients with lung cancer complicated by either IPF or ILA [6,7,33,34]. Our study also revealed that even equivocal ILA was associated with increased HRs for the development of AEIP.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, cause-specific HRs for AEIP were observed to increase sequentially with an increase in the ILA score. These findings are consistent with those shown in prior research that reported increased odds ratios for AEIP in patients with lung cancer complicated by either IPF or ILA [6,7,33,34]. Our study also revealed that even equivocal ILA was associated with increased HRs for the development of AEIP.…”
Section: Discussionsupporting
confidence: 93%
“…Our study also revealed that even equivocal ILA was associated with increased HRs for the development of AEIP. In previous studies, analyses of AEIP in patients with lung cancer were reported with frequencies or odds ratios based on logistic regression analyses [ 6 , 7 , 33 , 34 ]. However, studies of lung cancer generally censor their data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First‐line EGFR TKIs are the standard treatment in advanced EGFR ‐mutant NSCLC patients, improving response rates, progression‐free survival, and quality of life. 13 Shibaki et al 14 recently found that NSCLC patients with pre‐existing ILA shadows were more likely to develop TKI‐related lung injury, although survival curves for patients with and without lung injury were similar. This study also found that EGFR TKIs might be beneficial to EGFR ‐mutated NSCLC patients with ILA.…”
Section: Discussionmentioning
confidence: 99%